(untitled) (Communications in Mathematical Research, 2021)
We construct general structures of one and two variable interpolation function, without depending on the existence of divided difference or inverse differences, and we also discuss the block based osculatory interpolation in one variable case. Clearly, our method offers many flexible interpolation schemes for choices. Error terms for the interpolation are determined and numerical examples are given to show the effectiveness of the results.